2000
DOI: 10.1152/ajpregu.2000.279.3.r874
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the 24-h growth hormone profile to a state of sleep debt

Abstract: In normal men, the majority of GH secretion occurs in a single large postsleep onset pulse that is suppressed during total sleep deprivation. We examined the impact of semichronic partial sleep loss, a highly prevalent condition, on the 24-h growth hormone profile. Eleven young men were studied after six nights of restricted bedtimes (0100-0500) and after 7 nights of extended bedtimes (2100-0900). Slow-wave sleep (SWS) was estimated as the duration of stages III and IV. Slow-wave activity (SWA) was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
2
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 36 publications
2
87
2
2
Order By: Relevance
“…Sleep loss also reduces glucose clearance (114,119,120), and blood sugar remains at a high level during sleep instead of falling as is normal during wakefulness. (121)(122)(123).…”
Section: Stress and Sleep Physiologymentioning
confidence: 99%
“…Sleep loss also reduces glucose clearance (114,119,120), and blood sugar remains at a high level during sleep instead of falling as is normal during wakefulness. (121)(122)(123).…”
Section: Stress and Sleep Physiologymentioning
confidence: 99%
“…Sleep loss also dysregulates counter-regulatory hormones in a manner consistent with the promotion of hyperglycemia and/or insulin resistance. Indeed, elevations of evening cortisol levels (48-51), increased release of growth hormone and ghrelin during daytime hours (52)(53)(54), and elevated daytime levels of epinephrine (55) have all been observed under sleep debt conditions. Orexins A and B, two peptides that are synthesized by neurons concentrated in the LH, constitute a molecular link between sleep-wake regulation and the neuroendocrine control of appetite.…”
Section: Mechanistic Pathways Linking Central and Peripheral Control mentioning
confidence: 99%
“…Six hours of time in bed per night for a week or two brings the average young adult to the same level of impairment as 24 hours of wakefulness, whereas 4 hours of time in bed per night rapidly induces a level of impairment comparable with 48 hours of wakefulness (i.e., two consecutive days and nights without sleep). Metabolic studies have demonstrated that such sleep curtailment has adverse effects on the metabolic and immune systems as well (Spiegel et al 2000(Spiegel et al , 2002(Spiegel et al , 2004a(Spiegel et al ,b, 2005Mander et al 2001;Van Cauter et al 2007). Moreover, sleep loss interferes with memory consolidation and learning (Stickgold et al 2000;Walker et al 2002;Huber et al 2004;Walker and Stickgold 2004;Stickgold 2005).…”
Section: Chronic Sleep Restrictionmentioning
confidence: 99%